Synaptic Cell Adhesion Molecules in Alzheimer’s Disease - Iryna Leshchyns’ka; Vladimir Sytnyk (Neural Plasticity)
Alzheimer’s disease (AD) is a neurodegenerative brain disorder associated with the loss of synapses between neurons in the brain. Synaptic cell adhesion molecules are cell surface glycoproteins which are expressed at the synaptic plasma membranes of neurons. These proteins play key roles in formation and maintenance of synapses and regulation of synaptic plasticity. Genetic studies and biochemical analysis of the human brain tissue, cerebrospinal fluid, and sera from AD patients indicate that levels and function of synaptic cell adhesion molecules are affected in AD. Synaptic cell adhesion molecules interact with Aβ, a peptide accumulating in AD brains, which affects their expression and synaptic localization. Synaptic cell adhesion molecules also regulate the production of Aβ via interaction with the key enzymes involved in Aβ formation. Aβ-dependent changes in synaptic adhesion affect the function and integrity of synapses suggesting that alterations in synaptic adhesion play key roles in the disruption of neuronal networks in AD.